The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c8ra00750k
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial peptide KR-12 promotes the osteogenic differentiation of human bone marrow stem cells by stimulating BMP/SMAD signaling

Abstract: KR-12 is the smallest fragment of human antimicrobial peptide cathelicidin (LL-37), and could play key roles in the treatment of multiple infections, including osteomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
(102 reference statements)
0
18
0
Order By: Relevance
“…The TGF-β pathway consists of extracellular ligands, transmembrane receptors, and intracellular regulatory factors. The receptor TGF-β activates Smads and enters the nucleus, thereby regulating its target genes (Hui et al, 2018); the MAPK signaling pathway involves MAPK/ERK/big MAP kinase 1 (BMK1)/stress activated protein (SAPK)/c-Jun N-terminal kinase (JNK)/P38 in five main ways (Lou et al, 2019;Jiang et al, 2018). The MAPK signaling pathway also plays an important role in the proliferation, differentiation and apoptosis of osteoblasts (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β pathway consists of extracellular ligands, transmembrane receptors, and intracellular regulatory factors. The receptor TGF-β activates Smads and enters the nucleus, thereby regulating its target genes (Hui et al, 2018); the MAPK signaling pathway involves MAPK/ERK/big MAP kinase 1 (BMK1)/stress activated protein (SAPK)/c-Jun N-terminal kinase (JNK)/P38 in five main ways (Lou et al, 2019;Jiang et al, 2018). The MAPK signaling pathway also plays an important role in the proliferation, differentiation and apoptosis of osteoblasts (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Bormann et al reported high antimicrobial potency of some AMPs against bacteria both incorporated in a biofilm or internalized into cells with no harm to human osteoblasts [ 113 ]. Furthermore, Hui Li et al demonstrated that KR-12 - a fragment of human antimicrobial peptide cathelicidin LL-37 improves the osteogenic differentiation of human bone marrow mesenchymal stem cells via stimulating BMP/SMAD signaling [ 114 ]. Interestingly, Pavel Melicherˇcík et al reported that some antimicrobial peptides had lower minimum inhibitory concentrations (MICs) value than the two traditional antibiotics vancomycin and gentamincin but was found to be significantly more effective than those antibiotics when separately loaded into the calcium phosphate cement.…”
Section: Applications Of Amps In Some Infectious Diseasesmentioning
confidence: 99%
“…Moreover, KR-12 does not lyse human red blood cells unlike LL-37, which produces a certain hemolytic effect (Jacob et al, 2013; Mishra et al, 2013). Our previous studies demonstrated KR-12 to promote HBMSC osteogenic differentiation while possessing good antibacterial properties (Li et al, 2018). As an analogue of KR-12, KR-12-a5 (KRIVKLILKWLR) has been reported to exhibit better antibacterial properties against clinically resistant bacteria while maintaining good biocompatibility.…”
Section: Introductionmentioning
confidence: 98%
“…Since KR-12 and several other antibacterial peptides have the ability to promote stem cell differentiation (Krasnodembskaya et al, 2010; Alcayaga-Miranda et al, 2017; Milhan et al, 2017; Li et al, 2018), KR-12-a5 may also have the potential to promote HBMSC osteogenic differentiation. Associated with the excellent anti-inflammatory properties of this small peptide, KR-12-a5-mediated regulation of osteogenesis can be expected under inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%